Aspects of imagery in Catherine of Siena from a Jungian perspective - Munro, Alison Mary (Rhodes University, Faculty of Divinity, Department of Divinity, 2001)
This study investigates whether or nor not the imagery of Catherine of Siena can be interpreted from a Jungian perspective. It takes a lead from other studies, notably one on Teresa of Avila and Jung. Reading of medieval literature suggests that medievals applied the use of symbols and imagery in ways that are at times baffling to people of our time. Carl Jung was no stranger to imagery and symbol. In our current age with its renewed emphasis on the insights of spirituality, and to some extent its disenchantment with aspects of traditional psychology, there is room for a dialogue between the two disciplines of mysticism and psychology across a six-hundred year divide. The use of imagery, as a window to the soul, in the Christian tradition is examined. Catherine of Siena is situated within her own medieval context, one of upheaval in the church, but also an age of mysticism and spiritual/religious phenomena strange to our own time. Catherine is introduced against the background of her world and against the backdrop of the Dominican tradition. A discussion of some of her major imagery demonstrates her aim of union with God. An understanding of conscious aspects and of unconscious aspects of the self is shown as key to Jung ' s view of the psyche. Elucidation of some archetypes and a discussion of Jung's dream analysis demonstrates how Jung believed the unconscious becomes conscious, and how individuation becomes a possibility. Key Catherinian images are examined from a Jungian perspective. Catherine has relevance for the twenty first century, and we are invited to be challenged by the mysteries and truths to which her images point us.
Keywords: Catherine of Siena, Saint, 1347-1380; Christian Saints -- Italy; Jung, C G (Carl Gustav), 1875-1961